Cotton and polyester treated with tragacanth gum loaded with clove essential oil nanoemulsion for mosquito repellent - Abdullah, Nurul Nabila Aini; Kamari, Azlan; Wong, Siew Tin Susana; Yusof, Norjan; Othman, Hidayatulfathi; Hussein, Mohd Zobir; Hargreaves, Justin S. J. (Penerbit UTM Press, 2024)
Clove essential oil has been revealed to have a mosquito-repellent effect. Nevertheless, its application in topical preparations is minimal due to its immediate volatility. Nanoemulsion has been regarded as a promising carrier for essential oils. Here, we studied the effectiveness of cotton and polyester treated with tragacanth gum loaded with clove essential oil nanoemulsion to repel two mosquito species, namely Aedes aegypti (day biter) and Anopheles latens (night biter) for the first time. The nanoemulsion formulation was characterized using scanning electron microscopy, transmission electron microscopy, Fourier transform infrared spectroscopy, zeta potential and polydispersity index. Tragacanth gum loaded with clove essential oil nanoemulsion formulation exhibits 98% encapsulation efficiency with a-42.3 mV zeta potential and 0.3 polydispersity index. Following 5 cycles of washing, 60% of the tragacanth gum loaded with clove essential oil nanoemulsion retained on cotton meanwhile 46% of the nanoemulsion formulation retained on polyester. From an Excito chamber study, 64% of Ae. aegypti were successfully repelled from cotton whereas 53% of the same mosquito species were repelled from polyester. Overall, the nanoemulsion treatment was able to functionalize the fabrics up to a "very good" level of repellence against mosquitoes even after 5 cycles of washing. © 2024, Penerbit UTM Press. All rights reserved.